X : the experience when business meets design - Solis, Brian (John Wiley & Sons, 2015)
"Welcome to a new era of business in which your brand is defined by those who experience it. Customer experience is the new marketing and it's also one of the hottest trends in business right now. Also known as CX, executives, strategists, and agencies alike are learning that the digital customer is notably different than the traditional customers before them. Expectations, the technology they use, how and where they make decisions and what it is they value is forcing strategists to rethink and redesign the customer journey for a multiscreen world. While rife with challenges, CX represents a life-saving opportunity for businesses to earn relevance among a new generation of connected customers. But ... what is an experience? Believe it or not, it's more than creative marketing or exceptional customer support. An experience is a physical and emotional connection between brand and customer throughout the relationship lifecycle. An experience is the brand and it is aspirational. An experience is a great product, its packaging and its performance over time. An experience is delightful sales and service. An experience is everything and an experience is intentional by design The reality is that people are going to have an experience. The question is have we actually defined what it is and what it should look like, feel like, and how it enchants our senses and sensibilities? Or do you just leave it to chance? The problem is that experiences today are disjointed simply because everyone has a different answer to what an experience is or should be. And worse, people who lead customer engagement across different touchpoints don't collaborate or communicate today. Without design, experiences are indeed left to coincidence and there's no need, benefit or glory in happenstance. To compete for the future, to earn a competitive advantage and to build relevance into more meaningful and fruitful relationships, takes experience architecture. In his new book X, Brian Solis shares more than the importance of experience; he teaches readers how to design a desired, meaningful and uniform customer experience in every moment of truth. Solis introduces the rise of experience architecture and helps readers shift from a reactive to proactive approach to CX that borrows in a fun and informative way from the art and science of: User Experience (UX) Human-Centered Design Hollywood Storytelling Game Theory Transportation Engineering Storyboarding Apple's approach to experience architecture ... In X, Solis introduces a framework that will help anyone answer the question "What is an experience?" Business, meet design"--